Pemilihan Gaya Belajar untuk Meningkatkan Keaktifan Siswa dalam Pembelajaran Bahasa Indonesia - Riyanti, Asih; Sungkono (Universitas Wiralodra, 2020)
Every success in the learning process will affect environmental factors, schools, attitudes, or students themselves. Each student enhances cognitive, affective, and psychomotor development. Student trading has the uniqueness and character of each in the learning process to respond to and understand teaching material or information obtained. Student learning independence can be seen from the achievements of students in responding, solving, and processing information by completing various tasks. Every student has a learning style that is prominent in him, and the teacher must be able to accommodate it. That is to achieve the learning objectives well and effectively. Learning style is the key to student success in learning. There are models (Type) of learning styles (Fleming, 2001), VARK (Visual, auditory, Reading, Kinesthetic) that can increase student activity in learning Indonesian. Students can learn through the senses that they have with a visual learning style that learns from what is seen, students with an auditory learning style that is learning through what is heard, and a kinesthetic learning style that is learning through motion and opening.